Automated Analysis of X-Ray Images of the Temporomandibular Joint in Patients with Orthognathic Bite and Physiological Occlusion - M. A. Postnikov; O. V. Slesarev; D. A. Trunin; D. A. Andriyanov; S. N. Ispanova (Вестник рентгенологии и радиологии)
Objective: to propose a procedure for analyzing the X-ray image of the temporomandibular joint (TMJ) through the automated calculation of linear and angular measurements from craniometry points in comparison with the reference values.Material and methods. Fifty TMJ cone beam computed tomography images were analyzed in 25 volunteers aged 18-25 years with orthognathic bite and physiological occlusion. All the tomography images were analyzed from craniometric points, by using a section corresponding to the midsagittal plane of the TMJ. Angular and linear measurements characterizing the functional capacities of the TMJ were determined. A statistical analysis involved descriptive methods and was carried out by the IBM SPSS 21 statistics.Results. The introduction of automated estimation of TMJ functional capacities from angular and linear measurements made it possible to obtain the following data: the α-angle was 11.99±2.44° for the right TMJ and 12.12±2.78° for the left one; the β-angle was 11.58±2.31° for the right TMJ and 12.42±2.81° for the left one; the γ-angle was 156.41±4.57° for the right TMJ and 155.46±5.50° for the left one. A descriptive statistics checking revealed no gross errors.Conclusion. It is expedient to take into account the findings as reference values to characterize the anatomical and functional state of the TMJ on the x-ray image.